Dopamine-induced sulfatase and its regulator are required for Salmonella enterica serovar Typhimurium pathogenesis. Issue 3 (16th January 2019) - Das, Seema; Sreevidya, Virinchipuram S.; Udvadia, Ava J.; Gyaneshwar, Prasad
Abstract : Catecholamine hormones enhance the virulence of pathogenic bacteria. Studies in the 1980s made intriguing observations that catecholamines were required for induction of sulfatase activity in many enteric pathogens, including Salmonella enterica serovar Typhimurium. In this report, we show that STM3122 and STM3124, part of horizontally acquired Salmonella pathogenesis island 13, encode a catecholamine-induced sulfatase and its regulator, respectively. Induction of sulfatase activity was independent of the well-studied QseBC and QseEF two-component regulatory systems. S. Typhimurium 14028S mutants lacking STM3122 or STM3124 showed reduced virulence in zebrafish. Because catecholamines are inactivated by sulfation in the mammalian gut, S. Typhimurium could utilize CA-induced sulfatase to access free catecholamines for growth and virulence.